A matemática na trajetória pessoal e profissional: narrativas de professores iniciantes em um Programa Híbrido de Mentoria - Araújo, Natália Maria de (2022)
This study has as its theme the relationship between beginning primary school teachers, participants of the Hybrid Mentoring Program (PHM), with the learning and teaching of mathematics in their personal and professional trajectories. The research was based on a qualitative-descriptive methodological approach of the interpretative type, using as data production instruments collection of narratives written by three beginning teachers in the activities carried out in the virtual learning environment (AVA) throughout their participation in the PHM. The Program was an intervention-research developed by professors from the Federal University of São Carlos (UFSCar), between 2017 and 2020, which investigated the professional development of beginning and experienced teachers that worked in primary schools, based on the collaborative and constructive perspective by through a hybrid space, which, in addition to articulation virtual and face-to-face activities, promoted a non-hierarchical relationship, which made it possible to strengthen the relationship between university and school and professional practice the those involved. The theoretical bases of the research discuss learning about teaching, the training of teachers who teach mathematics, mathematics knowledge, knowing how to teach mathematics and the potential of narratives for research and teaching/training of teachers. The analysis was carried out in two categories: i) the references to the learning of mathematics, their teachers and teaching methodologies experienced in their personal trajectory as students, and ii) the formative demands presented regarding the teaching of mathematics and its development in the PHM. The results obtained revealed relationships with mathematics in the personal trajectory imbricated with emotional memories and also indicated a tendency of the mention mathematics in the schooling process by teachers who showed affinity with the area, also showing that the positive relationships with mathematics built as students throughout Elementary Education questioned in Higher Education. In the professional trajectory, the interations between each Beginning Teacher and their mentor exposed different relations with mathematics, such as: the knowledge needed to teach, the conceptions on problem solving and reflections on he the skills developed in the face of the impacts of the Covid-19 pandemic, subjects that were developed in a reflective perspective, favoring the improvement of the knowledge base for teaching. Understanding teaching as a complex profession and its professionals in constant development, there is a need to unveil relationships that teachers establish with mathematics in their personal and professional trajectory, valuing their uniqueness and contributing to their training.